Changes of family structure and treatment status of people with severe mental illness in rural China: a comparative study from 1994 to 2015. Issue 1 (October 2019) - Ran, Mao-Sheng; Peng, Man-Man; Yu, Yue-Hui; Zhang, Tian-Ming; Luo, Wei; Hu, Shi-Hui; Yang, Xin; Liu, Chang-Cheng; Liu, Bo; Liu, Ke-Zhi; Gong, Ke; Huang, Chao-Hua; et al.
Abstract: Background: Little is known about the relationship between changes of family structure for people with severe mental illness (SMI) and treatment status of SMI during a period of sustained rapid socioeconomic development. This study aimed to explore the relationship between changes of family structure and treatment status of people with SMI in a 21-year longitudinal study in a rural area of China. Methods: Epidemiological surveys of mental disorders were conducted in May, 1994, and October, 2015, in the same six townships (total population 170 174 in 2015) in Xinjin county, Chengdu, which is a representative middle-income rural county in southwest China. The six townships were randomly selected from all 12 townships of Xinjin county in 1994. The surveys consisted of two steps: (1) screening procedures for psychosis (face-to-face interviews with the head of each household together with key informant interviews), household by household; and (2) psychiatric interviews of people aged 15 years and older, to identify those with SMI (including schizophrenia, bipolar disorders, and major depressive disorder) according to the International Classification of Mental and Behavioural Disorders-10 (ICD-10) criteria. The two surveys were approved by the university human research ethics committees. Findings: The number of people aged 15 years and older who were identified to have SMI was 711 and 1042 in 1994 and 2015, respectively. The mean number of family members was significantly lower in 2015 (3·0 [SD 1·5]) than in 1994 (3·4 [1·5], p<0·0001). Compared with people with SMI in 1994, those with SMI in 2015 had a significantly higher rate of living alone (13·7% vs 9·9%, p<0·013) and without caregivers (15·6% vs 8·4%, p<0·0001). There was a significantly lower rate of parents as caregivers in 2015 than in 1994 (13·5% vs 17·9%, p<0·011). The rate of low family economic status (less than the population mean) for people with SMI was significantly higher in 2015 than in 1994 (p<0·0001). Fewer family members (included in the same family hukou) was significantly associated with low family economic status (p=0·023), and low family economic status was significantly associated with poor treatment status (p=0·015). Interpretation: The family structure and status of people with SMI has changed markedly during the rapid socioeconomic development from 1994 to 2015 in rural China. Fewer family members, fewer family caregivers and relative poverty have gradually become major challenges for families who care for people with SMI. How to improve care for people with SMI should be important if targets for Healthy China 2030 are to be met. Community mental health care, the precise poverty alleviation strategy, and the culture-specific family intervention programme should be crucial for comprehensive community mental health care and for improvement of the treatment and recovery of people with SMI in the community. Funding: The survey in 1994 was supported in part by the China Medical Board of New York (92-557). The survey in 2015 was supported in part by the Seed Funding Programme for Basic Research (2014–2016), Seed Funding Programme for Applied Research (2014–2016), Contemporary China Strategic Research Theme (2014–2016), Small Project Funding (2014–2016), and Mental Health Research in Chengdu, China (department matching fund, 2015–2017).